MAKNA PESAN BUDAYA MAKU GAWENE DALAM PERILAKU KOMUNIKASI ORANG TERNATE - Rakhmat Rakhmat (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Cultural messages are only captured with genuine appreciation and understanding by the cultural stakeholders themselves. The owner of culture will be able to feel the meaning because of living it in the environment even since childhood. This cultural message is then translated into values of life in society. The meaning contained in the cultural message of Maku Gawene contains about the principles of life to love each other, protect each other in the communication process. Simply Maku Gawene can be interpreted as a sense of mutual love and from this feeling is the basis for the formation of social solidarity as well as glue for any differences that exist. The meaning of Maku Gawene's cultural message then makes the communication behavior of Ternate people to be inclusive and full of love, so that they can accept others as part of them